ChemInform Abstract: A Catalyst‐Free, One‐Pot Multicomponent Synthesis of Spiro‐Benzimidazoquinazolinones via a Knoevenagel—Michael‐Imine Pathway: A Microwave Assisted Approach. Issue 36 (August 2016) - Maloo, Preeti; Roy, Tapta Kanchan; Sawant, Devesh M.; Pardasani, Ram T.; Salunkhe, Manikrao M.
Abstract: In this novel three‐component approach, the title compounds are simply prepared by short microwave‐heating.